2018
DOI: 10.3390/ijms19030811
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic and Apoptotic Activity of the Novel Harmine Derivative ZC-14 in Sf9 Cells

Abstract: Harmine, one of the natural β-carboline alkaloids extracted from Peganum harmala L., exhibits broad spectrum but limited insecticidal ability against many pests. So there is an urgent need to synthesize novel derivatives with high efficiency. In the present study, a new synthetic compound, [1-(2-naphthyl)-3-(2-thioxo-1,3,4-oxadiazol-5-yl) β-carboline] (ZC-14), showed a strong proliferation inhibition effect against the Spodoptera frugiperda Sf9 cell line in a dose-dependent manner. Simultaneously, apoptosis in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 55 publications
(59 reference statements)
0
6
0
Order By: Relevance
“…Our finding that β‐asarone induces apoptosis in Sf9 cells will help to elucidate the mechanism underlying its insecticidal activity. Recently, the ability of apoptosis induction in insect cells by many active compounds, including azadirachtin (Rembold & Annadurai, ), abamectin (Huang, Tian et al, ), harmine derivative ZC‐14 (Zhang, Zhang, Shu, Cui, & Zhong, ), spinosad (Yang et al, ), and camptothecin (Huang, Lv, Hu, & Zhong, ), suggesting that toxicity that induces apoptosis is conserved in many botanical insecticides. Azadirachtin is categorized as an antimitotic insecticide that targets cell division and cause proliferation inhibition and apoptosis in insect cell lines (Huang, Shui et al, ; Huang et al, ; Rembold & Annadurai, ; Salehzadeh et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that β‐asarone induces apoptosis in Sf9 cells will help to elucidate the mechanism underlying its insecticidal activity. Recently, the ability of apoptosis induction in insect cells by many active compounds, including azadirachtin (Rembold & Annadurai, ), abamectin (Huang, Tian et al, ), harmine derivative ZC‐14 (Zhang, Zhang, Shu, Cui, & Zhong, ), spinosad (Yang et al, ), and camptothecin (Huang, Lv, Hu, & Zhong, ), suggesting that toxicity that induces apoptosis is conserved in many botanical insecticides. Azadirachtin is categorized as an antimitotic insecticide that targets cell division and cause proliferation inhibition and apoptosis in insect cell lines (Huang, Shui et al, ; Huang et al, ; Rembold & Annadurai, ; Salehzadeh et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The hyphae were treated with a stain-fixative at 4 °C overnight, and then stained with 1 mL Hoechst 33258 solution (Beyotime) at 25 °C for 10 min after being washed twice with 0.1 M PBS. The samples were observed under a fluorescence microscopy [23].…”
Section: Methodsmentioning
confidence: 99%
“…β -carboline alkaloids are a class of natural and synthetic indole alkaloids with a wide range of pharmacological activities, including antitumor, antiviral, antiparasitic, and antibacterial activities [ 5 , 6 ]. Particularly, previous studies have shown that β -carboline alkaloids exerted antitumor activity through insertion into DNA [ 10 , 11 , 12 ], inducing apoptosis [ 13 , 45 ], inhibiting CDKs [ 16 ], and topoisomerase I and II activity [ 13 , 15 ]. The substitution at the C 3 and N 9 positions of β -carbolines could significantly increase their DNA insertion ability [ 7 ].…”
Section: Discussionmentioning
confidence: 99%